The Recipe for Corporate Longevity: From the Perspective of "Managing Innovation". Issue 16 (15th March 2018) - Griesar, Klaus; Bessant, John; Bernschneider‐Reif, Sabine
Abstract: The elephant is in the room—a metaphorical idiom for an obvious problem or risk that nobody wants to discuss. This abstract is not intended to be a summary, to reveal major findings, or unveil conclusions. On the contrary, it is aimed to provoke curiosity as to the question of corporate survival. Is there any recipe to be followed for companies to achieve this? The answer comes neither from the modest and traditional study rooms of philosophers nor the recent fact‐based studies from the offices (and well‐paid opinions) of business consultants. The Archimedean point from which we can objectively explore the subject of corporate survival does not exist. Instead we offer seven analogies (or metaphors) as intellectual platforms where new perspectives can be considered. Innovation obviously plays a major role in corporate survival—yet, by its nature all innovation is messy. In order to reduce entropy, this abstract reveals some keywords in alphabetical order starting from A, such as ambidexterity, architecture, and ant colonies, moving on to B, such as, (mental) boxes and biodiversity. For obvious reasons, C plays a major role—sufficiently that we have already revealed curiosity as one part of the answer—treading over to D (Darwin, DNA, and discontinuity), followed by E (earthquakes and evolution). As a final warning signal in order to manage the expectation: It is not the intention of this article to give a comprehensive overview about the rich and complex history of Merck KGaA, Darmstadt, Germany. Indeed, only the final chapter will provide reference to this company: Before the curtains will finally close, an epilogue will start in which one of the protagonists of the 350‐year journey of the company—Emanuel Merck—will appear on the stage and "let history speak for itself". Still curious? Abstract : Recipe for success : Is there any recipe to be followed for successful corporate survival? The answer comes neither from philosophers nor from business consultants. In this Essay, seven analogies (or metaphors) are offered as intellectual platforms where new perspectives for the longevity of a company can be considered. What can we learn from ant colonies, the ice industry, and the DNA of an organization?